A leitura literária nas Bibliotecas Monteiro Lobato de São Paulo e Salvador - Bortolin, Sueli [UNESP] (2001)
Child-youthful libraries are considered reader's mediator agencies; therefore, they perform an important role in society, specially in a developing country. On everyday, they have realized uncontable activities to promote reading. However, but it has also been noted that all the efforts are done in the name of reading actually lead to reading. So, this research has analysed the work done by Monteiro Lobato's libraries in São Paulo and Salvador concerning the promotion of reading. These information for analysis was gathered through bibliografic research and interviews at the libraries above mentioned. After these specialists in children-youthful libraries' opinions as far as concerned to the effectiveness and objectiveness af the activities intended to promote reading. It's conclued that the libraries accessed have similar actions in relationships to this promotion, demonstranting that the staff in both cases do not have a clear point of view on which activities do really lead to reading. It's expected that this study may subside everyone envolved and/or interested, in a way or another, for the formation af potential readers and the optimization of the libraries users... (Complete abstract, click electronic address below)